THE UTILIZATION OF THE COMPLETE RUMEN MODIFIER ON DAIRY COWS - Thalib, A.; Situmorang, P.; Mathius, I.W.; Widiawati, Y.; Puastuti, W. (Journal of the Indonesian Tropical Animal Agriculture, 2011)
An experiment on the use of Complete Rumen Modifier (CRM) to improve dairy cowproductivity and to mitigate enteric methane production has been conducted. Sixteen lactating dairycows were distributed into 4 groups by using compelete randomized design (CRD). Group I (Control)fed by basal diet consisted of elephant grass and concentrate 7.5 kg/hd/dy (CP 16% and TDN 70%),Group II (Pro. Woodii) fed by basal diet + probiotic Woodii, Group III (Pro.Noterae) fed by basal diet +probiotic Noterae; Group IV (CRM-Noterae) fed by basal diet + CRM + Pro.Noterae. Measurementswere conducted on body weight gain, average daily gain, feed conversion ratio, milk and methaneproduction. Results showed that CRM-Noterae increased ADG by 72% (1.29 vs 0.75 kg) and improvedFCR (9.2 vs 15.6). Probiotic noterae as single treatment or combined with CRM increased fat and totalsolid content of milk from 3.18% and 10.58% in control group to become 3.91%; 11.31% and 3.55%;11.02%, respectively. The lowest methane production was recorded in Group IV. The combination ofCRM and Noterae reduced percentage of methane production by 14%. It is concluded that combinationof CRM and Noterae can improve dairy cow performance and decrease methane production. ProbioticNoterae improved milk quality.